The The Implementation of Make a Match Method to Improve Students’ Vocabulary Mastery of Eighth Grade at MTsN Soppeng - Mursyid, Andi Hidayatul Mi'raj; Ramadani, Ria Reski (Fakultas Tarbiyah IAIN Fattahul Muluk Papua, 2024)
The objective of the research was to find out whether the use of Make a Match method can improve vocabulary mastery in terms of meaning, use, and form of the eighth grade students of MTsN Soppeng. The researcher applied pre-experimental method with one group pre-test and post-test design. The population of the research was the eighth grade students of MTsN Soppeng. The total sample of the research was 27 students. It was taken by using cluster random sampling. The data were collected through vocabulary test 9pre-test and post-test). To find out whether or not the implementation of reading short stories improves the vocabulary mastery of the eighth grade students of MTsN Soppeng, the researcher used t-test analysis. The result of the data analysis showed that there was a significant difference between pre-test and post-test. It can be seen from the result of statistical calculation where it showed that the value of sig (2-tailed) was smaller than the value a 0.05 (0.00<0.05). based on the finding and discussion of the study, the researcher concludes that use make a match method is able to improve vocabulary mastery of eighth grade students of MTsN Soppeng.